TREATMENT OF PREPAID EXPENSES ON THE CASH BASIS OF ACCOUNTING. - Rabinowitz, Sidney I. (The Accounting Review, 1940)
Abstract Criticized and condemned but never thoroughly analyzed, the cash basis of accounting remains a relatively unexplored field of accounting theory. At the hands of the text writers, it has received meager treatment indeed. The perfunctory treatment may be adequate because the cash basis is a simple concept whose application is readily apparent. The writer hopes that this article will dispel that illusion. Indeed, an adequate treatment of all problems lurking in a comprehensive analysis of the cash method is too ambitious a project. The article is therefore confined to one small segment of the problem: the treatment of prepaid expenses. Suggestions changing the practice in respect of the cash method have not been lacking. For the most part, these have been confined to limiting its scope. Indeed, it has been forcefully suggested that it be entirely abolished in Federal income taxation. There is this to be said in favor of the abolition or serious curtailment of the cash method. It allows the taxpayer a greater degree of control over the amount of disbursements and thereby over the amount of taxable net income in any particular year.